UJI KUALITATIF KANDUNGAN KARBOHIDRAT DAN PROTEIN PADA BAHAN PANGAN HEWANI DAN NABATI MENGGUNAKAN METODE BIOKIMIA SEDERHANA - Bima Reksa Kumala; Dedi Damhuri (Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2026)
Carbohydrates and proteins are essential macronutrients that play important roles in body metabolism and human nutritional needs. This study aimed to identify the carbohydrate and protein contents in various animal- and plant-based food materials using simple biochemical methods, namely Lugol and Biuret tests. The study employed a qualitative descriptive method with samples consisting of tofu, tempeh, milk, banana, catfish, beef, chicken meat, egg, avocado, and peanuts. Sample preparation was carried out by homogenizing the food materials and adding distilled water to obtain filtrates for testing. The Lugol test was performed to detect starch content based on the formation of a blue-black color, while the Biuret test was used to detect proteins through the formation of a purple Cu–peptide complex. The results showed that banana gave a positive result in the Lugol test indicated by a dark coloration, suggesting the presence of starch, whereas most other samples showed negative results. In the Biuret test, tofu, tempeh, milk, catfish, beef, chicken meat, egg, and peanuts showed positive results indicated by a purple color change, confirming the presence of protein. This study demonstrates that Lugol and Biuret tests can be used as simple, rapid, and effective methods for the preliminary identification of carbohydrate and protein contents in food materials.